EVALUATION OF THE FREE NUTRITIOUS MEAL PROGRAM (MBG) IN ELEMENTARY SCHOOLS: A REVIEW OF IMPLEMENTATION, BENEFITS, AND CHALLENGES - Enong Holilah (http://jurnal.untirta.ac.id/index.php/JTPPm, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is one of Indonesia’s national priority programs aimed at improving community nutritional status, particularly among students, as part of efforts to develop high-quality human resources toward the Indonesia Golden Vision 2045. This study aims to evaluate the implementation of the Free Nutritious Meal Program at the elementary school level using the CIPP (Context, Input, Process, Product) evaluation model. The study employed a qualitative descriptive approach through a literature review method. Data were collected from secondary sources, including program guidelines, evaluation documents, government reports, and relevant scientific publications. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that, in terms of context, the MBG Program is highly relevant to students' nutritional needs and national development goals. Regarding input, the government has provided regulations, funding, human resources, and implementation mechanisms that support the program's success. In terms of process, the program has generally been implemented well, although several challenges remain, including unequal food distribution, limited supporting facilities, and the need for stronger food safety supervision. Regarding product, the program has positively contributed to meeting students’ nutritional needs, improving learning concentration, increasing school attendance, and enhancing the quality of educational services. However, strengthening monitoring and evaluation systems, improving the capacity of program managers, and standardizing service quality remain necessary to enhance program effectiveness. Overall, the Free Nutritious Meal Program demonstrates significant potential to support sustainable improvements in students’ health and educational outcomes